Superhydrophobic and High Transmittance Coated Silica Aerogel Prepared in Ambient Pressure as Self-Cleaning Windows - Mahdi, Huda Salh; Al-sharuee, Israa F. (Al-Mustansiriyah Journal of Science, 2026)
Background: Highly porous nanomaterials have been promising materials in recent years. Silica-based materials have attracted the attention of researchers because they are easy to prepare under normal atmospheric pressure. Furthermore, they have broad practical applications that aim to reduce time and cost. Objective: The current work highlights self-cleaning windows for high buildings that are difficult to access. Hydrophobic silica was prepared, and the surfaces of regular glass were coated with gel during the preparation process, taking into justification that the transparency of the glass would not be affected. Methods: The preparation was carried out under normal atmospheric pressure and for a period of only one week, during which samples of hydrophobic silica were prepared with ratios of the starting material tetraethylorthosilicate (TEOS), ethanol, and hydrochloric acid with 0.5 molar concentration, and taking into account the molar ratios in each case for each of TEOS:ethanol:HCl at ratios of 1:5:0.2. Results: The results of the UV test showed that the transparency ratios of samples changed slightly with a variation when the TEOS ratios were changed. The best result was 95% at pH7 with a volume ratio of 1 TEOS. The contact angle was within the superhydrophobic region at 152° and was best at a value of 1TEOS at pH7. This was confirmed by the FTIR test through the weak beams that return to OH, Si-OH, and H-OH groups. Also, the AFM images showed that the roughness ratios are very good, which enhances the role of the prepared models in practical applications. The differential thermal‐thermogravimetric TGA-data test also confirmed the stability of the samples at a temperature of 217 °C. This is particularly important, as glass is exposed to varying temperatures throughout the year. Conclusions: It can be confirmed that it is possible to obtain superhydrophobic silica coated on glass slides, which exhibit high transparency and thermal stability. This enables it to withstand external conditions such as high temperatures, rain, and dust. Therefore, it is easy to produce self-cleaning glass covers or windows that are resistant to heat and humidity.